2018
DOI: 10.1016/j.cell.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

A Network of Noncoding Regulatory RNAs Acts in the Mammalian Brain

Abstract: SUMMARY Noncoding RNAs (ncRNAs) play increasingly appreciated gene-regulatory roles. Here, we describe a regulatory network centered on four ncRNAs—a long ncRNA, a circular RNA, and two microRNAs—using gene editing in mice to probe the molecular consequences of disrupting key components of this network. The long ncRNA Cyrano uses an extensively paired site to miR-7 to trigger destruction of this microRNA. Cyrano-directed miR-7 degradation is much more effective than previously described examples of target-dire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

31
582
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 524 publications
(617 citation statements)
references
References 69 publications
(124 reference statements)
31
582
2
2
Order By: Relevance
“…The interaction between ciRS-7 and miR-7 can be affected by miR-671 and the long non-coding RNA (lncRNA) Cyrano (Kleaveland et al 2018). Compared to the extensive, but only partially complementary binding sites of miR-7 in ciRS-7, there is a single, highly complementary site between miR-671 and ciRS-7 (Piwecka et al 2017).…”
Section: Circrnas In Neurological Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between ciRS-7 and miR-7 can be affected by miR-671 and the long non-coding RNA (lncRNA) Cyrano (Kleaveland et al 2018). Compared to the extensive, but only partially complementary binding sites of miR-7 in ciRS-7, there is a single, highly complementary site between miR-671 and ciRS-7 (Piwecka et al 2017).…”
Section: Circrnas In Neurological Disordersmentioning
confidence: 99%
“…In addition, ciRS-7 can be modulated post-transcriptionally. The long non-coding RNA Cyrano can promote unusually efficient degradation of mature miR-7, prevent repression of miR-7-targeted mRNAs, and enable accumulation of ciRS-7 in the mouse brain (Kleaveland et al 2018). These studies suggest that circRNAs may play an important role in normal and pathological mammalian brain function, which is implicated in many disorders in CNS including Alzheimer's disease (AD), Parkinson's disease (PD), ischemic brain injury, neurotoxicity, and cancer.…”
mentioning
confidence: 99%
“…In our previous work, we analysed the function of this pathway in pulmonary fibrosis under astilbin action 12. Kleaveland et al recently reported that three different classes of ncRNAs converge in a regulatory network whereby an lncRNA represses an miRNA via target-directed miRNA degradation, which in turn enables the accumulation of a circRNA in the mouse brain 45. This finding has once again proved that various…”
mentioning
confidence: 73%
“…The past decade has experienced a remarkable increase in the understanding of miRNA biogenesis, their target genes, miRNA biomarkers and potential therapeutics for a growing number of disease conditions. RNA-based markers and therapeutics have a potentially significant clinical impact, and many of the miRNA-based therapies are at various stages of application and human clinical trial [2].As background, non-coding RNAs are divided into (i) transcription RNAs (including both tRNA and rRNA); (ii) small RNAs, which are further subdivided into siRNAs, miRNAs, snoRNAs, and snRNAs; and (iii) most recently, long non-coding RNAs, which are now know to transcribe short peptides [3]. MicroRNAs are single-stranded non-coding RNAs that are typically 18-25 nucleotides (nts) in length and are best known for their role in the post-transcriptional regulation of gene expression.…”
mentioning
confidence: 99%
“…As background, non-coding RNAs are divided into (i) transcription RNAs (including both tRNA and rRNA); (ii) small RNAs, which are further subdivided into siRNAs, miRNAs, snoRNAs, and snRNAs; and (iii) most recently, long non-coding RNAs, which are now know to transcribe short peptides [3]. MicroRNAs are single-stranded non-coding RNAs that are typically 18-25 nucleotides (nts) in length and are best known for their role in the post-transcriptional regulation of gene expression.…”
mentioning
confidence: 99%